Injury rates following the COVID-19 lockdown: A case study from an UEFA futsal champions league finalist - Konstantinos Spyrou; Pedro E. Alcaraz; Elena Marín-Cascales; Rubén Herrero-Carrasco; Lucas A. Pereira; Irineu Loturco; Tomás T. Freitas (Elsevier, 2022)
Introduction: Recently, a pandemic disease (i.e., COVID-19) arose complicated conditions for players, clubs, and sports competitions. Most European countries postponed or canceled their respective leagues as players were forced into a long-term lockdown. This case study presents and compares the absolute and relative non-contact lower-limb injury rates and characteristics before and after the lockdown from a Finalist of the UEFA Futsal Champion League. Material and methods: Thirteen elite futsal players (age: 27 ± 2.8 years old; body mass: 76 ± 5.4 kg; height: 1.79 ± 0.1 m; body fat: 9 ± 1.6%) participated in this study. Injury severity, location, type, and mechanism were recorded. Data from the 6 weeks pre- and post-lockdown were collected, and injury rates were expressed per 1,000 training and match hours. Results: Chi-Square tests revealed a significant difference (p = 0.039) in the distribution of the number of injuries between the two moments. No overuse and non-contact injuries were observed during the 6 weeks before the lockdown. Nevertheless, 38% (i.e., 5) of the players suffered minimal severity (i.e., ≤ 3 days of court absence) overuse injuries in the hip/groin and thigh muscles post-home-confinement. Conclusions: Elite male futsal players sustained a substantially higher number of lower-body non-contact injuries after the lockdown. Practitioners should implement a thorough analysis of players' neuromuscular qualities and fatigue to identify individual training and recovery needs and, thus, prescribe more tailored injury-reduction programs.